Efektivitas Perlindungan Hak Kekayaan Intelektual Dalam Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Ferry, Muhammad (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
This study examines the effectiveness of Law Number 28 of 2014 on Copyright in addressing book reproduction practices as part of protecting citizens’ intellectual property rights. The research aims to assess the practical effectiveness of the law, identify factors influencing its implementation, and formulate strategies to strengthen legal protection. An empirical legal method with a sociological approach is employed, viewing law through community practices and the performance of enforcement institutions. The findings indicate that book reproduction constitutes copyright infringement when it is conducted for economic gain. Although the law is normatively adequate, its implementation remains suboptimal due to inconsistent enforcement actions and limited public outreach by the government. Infringement is also influenced by low legal awareness, a preference for photocopied books driven by affordability, and insufficient understanding of the legal consequences of copyright violations. This study underscores the need to strengthen law enforcement, expand continuous public education, and improve inter-agency coordination to enhance effective copyright protection, particularly for authors and creators